PERSEPSI SISWA TERHADAP PEMBELAJARAN BIOLOGI PADA KURIKULUM 2013 EDISI REVISI 2018 - Dede Irvandi (FKIP Universitas Tanjungpura, 2022)
To achieve the expected educational goals, a curriculum wass needed that can help the learning process run smoothly. The implementation of a curriculum would certainly had an impact on students, their perceptions on the perceptions of each student, especially in biology subjects. The aims of this study was determine students' perceptions in the biology learning process by teachers related to the applied curriculum. This study used a qualitative approach with a descriptive method which was a descriptive feature to describe the status of a phenomenon and was also a qualitative research, namely to see the perceptions of class XI students including teaching and learning activities that occur in the classroom. Observations show that SMA Negeri 2 Menyuke had implemented the use of the 2018 revised 2013 Curriculum which had four aspects of learning, namely Strengthening Character Education, Literacy, 4C (Communication, Critical Thinking, Creativity, and Collaboration), and HOTS (High Order Thinking Skill) which in total, students' perceptions of biology learning were 74.51% which was classified as good.